Trust and the Spirit: The Canon's Anticipated Unity - Helmer, Christine (Journal of theological interpretation, 2007)
How can one talk responsibly and theologically about the biblical canon's unity in a pluralist age? In this article I explore a number of ways in which theological practice both appeals to and constructs the canon's unity. The argument of section one addresses biblical, not canonical, unity. I distinguish between the Bible as a given text composed of multivalent layers, individual texts, genres, and a plurality of content; and the canon as a theological concept, which is analytic with unity. The theological arguments of sections two and three situate the theological construction of the canon's unity in view of biblical multivalence. Some theological issues are at stake in this relation. Biblical multivalence opens up theological, philosophical, and ethical questions concerning how different proposals of the canon's unity can coexist, while each making claims to truth. Truth criteria—for example, coherence and comprehensiveness—can be worked out in order to determine the validity and viability of different theological proposals. A proposal must also be evaluated on the basis of its adequacy to contemporary concerns. The complex process of forming theological judgments about the canon's unity contextualizes the selection of one proposal of unity, among others, in a particular matrix of contemporary concerns. Hence, the unity of the canon is anticipatory in view of the process of articulating theological judgments in various contexts. I conclude by proposing that unity and multivalence can be grasped together in the intersubjective orientation to truth that takes place in trust, established by the Holy Spirit.